Biomechanical differences of cycle pedaling according to uphill slope - Kim, D.-H.; Yoon, S.-H. (Korean Journal of Sport Biomechanics, 2024)
Objective: The purpose of this study is to provide quantitative data through biomechanics analysis of lower extremity movements according to uphill slope when pedaling a cycle. The method of the study were as follow. Method: Ten healthy adult males (age: 30.18 ± 4.2 yrs., height: 173.75 ± 2.99 cm, weight: 66.9 ± 2.64 kg), and who have a weekly exercise distance of more than 100 km and participated in amateur competitions with no lower extremity musculoskeletal injury within the past six months participated in this study. The experiment was conducted at three uphill slopes of 8%, 14%, and 20%, and the intensity of the experiment was 5.5 to 6 watts per kg of body weight for each slope for 4 minutes. A 3-Dimensional motion analysis with eight infrared cameras (sampling rate: 200 Hz) and five-channel of EMG (sampling rate: 2,000 Hz) was performed. In this study event 1, 2, 3, and 4 were set at angular position of pedal at 330°, 30°, 150° and 210°, respectively. Also connections of events were set as phases (P1~P4). A one-way ANOVA with repeated measures was conducted to verify the intervention effect and the statistical significance was set at a=.05. Results: As the uphill slope increased, the position of COM moved further back from the center of the cycle. In the knee joint, P1 and P3 showed greater ROM and higher angular velocity as the slope increased, while P2 and P4 showed opposite results. As the slope increased the peak activation timing was found to be faster for the vastus lateralis and biceps femoris, while the peak activation timing for the medial gastrocnemius muscle was delayed. Conclusion: There was a difference in kinematics as the uphill slope increased during cycling, and the difference between 8% and 14% showed a greater change than the difference between 14% and 20%.